[PP.20.02] FACTORS AFFECTING MYOCARDIAL PERFUSION IN PATIENTS WITH RHEUMATOID ARTHRITIS. (September 2016) - Anyfanti, P.; Triantafyllou, A.; Triantafyllou, G.; Panagopoulos, P.; Koletsos, N.; Pyrpasopoulou, A.; Chatzimichailidou, S.; Gkaliagkousi, E.; Aslanidis, S.; Douma, S.
Abstract : Objective: Rheumatoid arthritis is associated with increased cardiovascular mortality and morbidity. Subendocardial viability ratio (SEVR) is a widely accepted, non invasiveindex of myocardial perfusion relative to cardiac workload. We investigated predictors of SEVR in rheumatoid arthritis patients among a wide range of hemodynamic parameters and indices of inflammation, atherosclerosis, macrovascular and endothelial dysfunction. Design and method: Among consecutive patients attending the Rheumatology Outpatient Unit of our Department, SEVR was calculated as the ratio of the diastolic pressuretime index and the systolic pressure time index from radial artery pressure waveforms using applanation tonometry (SphygmoCor, AtCor Medical, Ltd., Sydney, Australia). Arterial stiffness was estimated with measurement of carotid-femoral pulse wave velocity (PWV) with the same device. Carotid ultrasound was used for the estimation of mean carotid intima-media thickness (cIMT). All participants underwent impedance cardiography for the evaluation of hemodynamic parameters, including stroke index (SI), cardiac index (CI), thoracic fluid content index (TFCI), and systemic vascular resistance index (SVRI). Blood sampling was performed for the evaluation of inflammatory markers, lipid fractions and asymmetric dimethylarginine (ADMA), a nitric oxide synthase inhibitor indicative of endothelial dysfunction. Results: A total of 96 rheumatoid arthritis patients, 75 females and 21 males aged 62.2 ± 11.5 years were included. Mean SEVR was 141.4 ± 21.9% and was significantly higher among males compared to females (150.9 ± 24.0 vs 138.7 ± 20.7% respectively, p = 0.048). SEVR significantly correlated in the univariate analysis with CI (r = –0.292, p = 0.005) and office heart rate (r = –0.517, p < 0.001) and a trend was observed with cIMT (p = 0.052), total cholesterol (p = 0.052), LDL (p = 0.065), SVRI (p = 0.064), but not with PWV, SI, TFCI, ADMA, TKE, CRP and disease activity or duration (p > 0.05 for all). However, in the multiple regression analysis, total cholesterol (p = 0.002), sex (p = 0.006), systolic blood pressure (p = 0.010), heart rate (p < 0.001), and CI (p = 0.011) were identified as independent predictors of SEVR. Conclusions: Hemodynamic parameters, gender and dyslipidemia appear to exert a negative impact on myocardial workload in patients with rheumatoid arthritis. The detrimental effects of inflammation, macrovascular impairment and endothelial dysfunction on the cardiovascular system do not seem to be primarily mediated through altered subendocardial perfusion in rheumatoid arthritis patients.